The determinants of capital structure towards leverage of listed property companies in Malaysia / Mohd Hasrol Hassan Basri - Hassan Basri, Mohd Hasrol (2014)
The aim of this study is to answer the question: ‘do board diversity affect the company’s performance?’. There are five board diversity characteristics that have been studied in this research. There are gender, ethnic, nationality, age and the size of the board. Return on Assets (ROA) is used as a measurements for firm financial performance. There are 28 companies being selected which the characteristics are the Government Linked Companies (GLCs) and they are listed in Bursa Malaysia between 2008 and 2012. The results show that size of board and average age of directors have positive relationship between ROA while gender, ethnic and nationality of the directors have negative relationship with ROA.